2004
DOI: 10.1128/jb.186.12.4014-4018.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Regulation in Vibrio parahaemolyticus : Compensatory Activation of Polar Flagellar Genes by the Lateral Flagellar Regulator LafK

Abstract: Gene organization and hierarchical regulation of the polar flagellar genes of Vibrio parahaemolyticus, Vibrio cholerae, and Pseudomonas aeruginosa appear highly similar, with one puzzling difference. Two 54 -dependent regulators are required to direct different classes of intermediate flagellar gene expression in V. cholerae and P. aeruginosa, whereas the V. parahaemolyticus homolog of one of these regulators, FlaK, appears dispensable. Here we demonstrate that there is compensatory activation of polar flagell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…parahaemolyticus and some A. hydrophila strains express dual flagellum systems, and LafK is the lateral-flagellum master regulator (8,39). In V. parahaemolyticus LafK is able to compensate for the mutation of the polar-flagellum 54 -dependent response regulator FlaK (19). Data obtained are consistent with the fact that the A. hydrophila FlrA mutation abolishes polar-flagellum formation in liquid and solid media but does not affect inducible lateral-flagellum formation (7).…”
Section: Vol 193 2011supporting
confidence: 76%
See 1 more Smart Citation
“…parahaemolyticus and some A. hydrophila strains express dual flagellum systems, and LafK is the lateral-flagellum master regulator (8,39). In V. parahaemolyticus LafK is able to compensate for the mutation of the polar-flagellum 54 -dependent response regulator FlaK (19). Data obtained are consistent with the fact that the A. hydrophila FlrA mutation abolishes polar-flagellum formation in liquid and solid media but does not affect inducible lateral-flagellum formation (7).…”
Section: Vol 193 2011supporting
confidence: 76%
“…One open reading frame of lateralflagellum clusters of both species encodes a 54 -dependent response regulator, LafK, essential for lateral-flagellum generation (8,39). V. parahaemolyticus LafK is able to compensate for mutation of the polar-flagellum 54 -dependent response regulator, FlaK (19). The A. hydrophila FlrA mutation abolished polar-flagellum formation but did not affect lateral-flagellum-dependent swarming motility on semisolid medium; furthermore an A. hydrophila LafK mutation that abolished lateral-flagellum formation did not affect polar-flagellum biogenesis (7,8).…”
mentioning
confidence: 99%
“…Additionally, the transcriptional hierarchy of the PF and LF systems has been shown to be specific with no interconnections1524. Although compensatory activation of PF genes by the LF regulator LafK has been demonstrated11, genetic experiments in V. parahaemolyticus , which has a dual flagellar system, suggested that there are no shared structural components among the two motility systems and that mutants unable to swarm retain swimming motility and vice versa10. An investigation of the dual flagellar system of Shewanella putrefaciens CN-32 also demonstrated that the motor components were highly specific and were unlikely to be shared between the two flagellar systems19.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations affecting PF performance resulted in the production of LF in liquid medium10. Moreover, the LF regulator LafK could influence the expression of PF genes by compensatory activation11. Nevertheless, the relationship between the polar and lateral flagellar structural genes is still largely unknown.…”
mentioning
confidence: 99%
“…9 We used either laf-mutants or the control of growth conditions to produce purified pof. 9,10 In an earlier paper, we named the major flagellar polymorph observed under physiological conditions left-handed curly (or L-Curly). However, this form would be called N by Leifson's definition, because it is the commonest polymorph under ordinary conditions.…”
Section: Polar Flagella Belong To Family IImentioning
confidence: 99%